EFFICACY OF URSODEOXYCHOLIC ACID FOR MANAGEMENT OF INTRAHEPATIC CHOLESTASIS DURING PREGNANCY - Tanzeela Bano; Aisha Iqbal; Ghazala Iftikhar; Mahwash Jamil (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Intrahepatic cholestasis of pregnancy is a pregnancy-specific liver disorder. This condition is characterized by symptoms of maternal pruritus in the third trimester of pregnancy. It is associated with raised serum bile acids and increased rates of adverse fetal outcomes.   Ursodeoxycholic acid is currently the most effective treatment for intrahepatic cholestasis and is thought to reduce pruritus and neonatal complications. Ursodeoxycholic acid treatment should be recommended for women with intra hepatic cholestasis during Pregnancy to reduce adverse maternal and fetal outcomes. Rationale of this study is to assess the efficacy with UDCA for management of females presenting with intrahepatic cholestasis.Methodology: A descriptive cross sectional study was conducted in the department of Obstetrics and Gynecology, services hospital, Lahore. The ethical approval was obtained from IRB of institute and study was done from 15th January 2022 to 15th June 2022. The 150 pregnant females with cholestasis were included in study through consecutive sampling. Demographic information (including name, age, gestational age, parity and contact) was also recorded. Females were given UDCA capsules (250 mg QID dose). Then females were followed-up in OPD for 20 days. If female report of absence of pruritus, then drug efficacy was labelled. Quantitative data like age and gestational age was presented as mean and standard deviation. Qualitative data like parity and efficacy was presented as frequency and percentage. Data was stratified for age, gestational age at presentation and parity. Post-stratification, chi-square test was applied with p-value≤0.05 as significant.Results: In this study, the mean age of the women was 28.59 ± 6.84 years. Regarding parity, 35 women (23.3%) were primiparous, and 30 women (20%) had a parity of 1. The remaining 85 women (56.66%) were multiparous. The efficacy of ursodeoxycholic acid (UDCA) in treating intrahepatic cholestasis of pregnancy (ICP) was observed in 88 women (58.7%).Conclusion: This study showed satisfactory treatment efficacy of UDCA for treating Intrahepatic Cholestasis in pregnancy by improving pruritus within 20 days of initiation of treatment.